Students' Constructions of a Christian Future: Faith, Class and Aspiration in University Contexts. (February 2017) - Guest, Mathew; Aune, Kristin
Economic uncertainties have unsettled the status of higher education as an assured means to social mobility, raising questions of how students orient themselves to life after graduation. In this context, how does religion (a neglected aspect of student identity) shape students' attitudes and plans? This article examines the future aspirations of Christian students, theorising Christian identity as an inter-subjective resource through which 'alternative' futures are imagined, a resource variously framed by classed assumptions about propriety. It analyses data from 75 interviews with undergraduates at five English universities, and explores emerging aspirational paradigms structured around hetero-normative domesticity, the formation of Christian counter-narratives to contemporary capitalism and positive submission to God.